INCORPORATING TECHNOLOGY IN TEACHING: AN ANALYSIS OF SENIOR HIGH SCHOOL ENGLISH TEACHERS’ PROFICIENCY BASED ON BLOOM’S DIGITAL TAXONOMY FRAMEWORK - Ni Luh Ari Artini (International Journal of Instructions and Language Studies, 2025)
This study investigated the proficiency level of Senior High School English teachers in integrating technology based on Bloom’s Digital Taxonomy (BDT) framework and factors influencing teachers’ proficiency. This study employed explanatory sequential research design where the data were gathered through quantitative data (questionnaire) and qualitative data (observation, interview, document analysis). The data were gathered through five Senior High Schools of North Denpasar area with 19 English teachers. The data further analysed to find the index and average score of the questionnaire. Then, the questionnaire was further analysed through the result of observation, interview and document analysis by implementing data condensation, data display and data interpretation. This study resulted that the proficiency level of teachers was in C3-Applying level. The factors found in influencing teachers’ proficiency level are: 1) External factors are consisted of curriculum demand, teachers’ workload, school infrastructure, and digital training, and 2). Internal factors are consisted of self-motivation and self-learning, years of teaching experience and educational background. The proficiency level of teachers also relates with in which aspect of TPACK the teachers are. It was found that TPK became the most frequent TPACK aspect implemented by teachers. To conclude, this study also derived into several suggestion for future researchers, namely investigate this topic in the different area of Bali with larger sample size, explore the students’ perspectives of the technology integration, as well as investigate the adequate digital training program for teachers.